Housing price, family structures and household consumption: Empirical evidence of Taiwan - Hung, Chih-Hsing; Chen, Yen-Hung; Cheng, Chung-Chieh; Tzang, Shyh-Weir (International Journal of Strategic Property Management, 2024)
The housing price affects the allocation of family budget on consumption. We use regression analysis to confirm whether Taiwan’s housing prices have a significant influence on household consumption based on the questionnaire survey on household income and expenditure in 2018. We find that housing prices have the greatest impact on household consumption, possibly because housing accounts for the largest proportion of household assets, implying a significant wealth effect. In addition, the impact of interest of deposit on consumption is also found to be greater than that of household income as it is related to the level of total assets. The housing prices for single-person household with female gender have a negative and significant impact on household consumption. Finally, housing prices are found to have a significantly negative effect on non-consumption and current transfer expenditure. The possible reason is that the households who hold the house believe that the appreciation of housing price can provide more protection for the family from suffering from possible economic risks in the future and thus crowd out non-consumption expenditures.